Second-Order Duality for a Class of Nondifferentiable Continous Programming Problems (European Journal of Pure and Applied Mathematics, 2012)
A dual problem associated with a class of non-differentiable continuous programming problemsis formulated. Under the second-order pseudo-invexity, various duality theorems are validated for this pair of dual problems. A pair of dual problems with natural boundary values is constructed and the proofs of its various duality results are merely indicated. Further, it is shown that our results can be viewed as dynamic generalizations of corresponding (static) second-order duality theorems fora class of nondifferentiable nonlinear programming problems existing in the literature.